Laser-activated voltammetry: measurement of the diffusion coefficients of electropassivating species. Application to pyrrole and phenol in aqueous solution - Fulian, Q; Compton, R (2000)
Clean electrode surfaces can be achieved during the electrolysis of otherwise passivating species in aqueous and other solutions by means of surface ablation using a 10-Hz pulsed Nd:YAG 532-nm laser. This ability to remove passivating electrolytically generated layers on glassy carbon and platinum electrodes is shown first by an investigation of the stripping peaks formed from the electrogeneration of the neutral forms of methyl viologen and heptyl viologen during reduction in aqueous solution of dications. Next, laser ablation was conducted under well-defined hydrodynamic conditions using a channel flow cell to identify laser power thresholds below which transport-limited currents could be seen, which were in quantitative agreement with those expected in the absence of irradiation. Levich plots recorded in the channel flow cell for K4Fe(CN)6 at glassy carbon and platinum electrodes showed such agreement for laser intensities lower than 0.17 and 0.65 W cm(-2), respectively. Working at intensities below these thresholds, steady-state voltammetry was observed for the oxidation of both phenol and pyrrole at glassy carbon and platinum electrodes, respectively, in aqueous solution. The diffusion coefficients of these two species were then measured under hydrodynamic conditions using laser ablation voltammetry to continuously clean the surface. Diffusion coefficients were inferred using the Levich equation. The result for phenol at a pH of 12 in aqueous solution was 0.9 (+/-0.1) x 10(-5) cm2 s(-1), which is in good agreement with an independent nonelectrochemical method. The diffusion coefficient of pyrrole in aqueous solution was similarly evaluated as 1.25 (+/-0.1) x 10(-5) cm2 s(-1).